Microbial diversity above a shale gas field using high-throughput sequencing - Lei GU; Kewei XU; Yuping TANG; Fan YANG; Guojian WANG; Wei DU; Bo GAO; Tenger BORJIGIN (Shiyou shiyan dizhi, 2020)
In recent years, microbial analysis has become a new detection technology in oil and gas surface exploration. The microbial diversity above a shale gas field was studied in order to further understand microbial information. High-throughput sequencing technology was used to study the abundance and diversity of hydrocarbon species in a shale gas field in the Dingshan area of the southeastern Sichuan Basin. Three main microorganisms were identified, including Methylophilales, Methylocystis, and Methylococcus, which are worthy of further biochemical research and can be used as potential oil and gas indicating bacteria. The developmental abundance of three kinds of microorganisms has a good matching relationship with the distribution of the fugitive area in Dingshan. The high-throughput analytical technology can be applied well in the study of oil and gas microorganisms in Dingshan area, and the distribution characteristics of microorganisms in bedrock samples were obtained. Furthermore, a preliminary analysis of the differences between oil and gas microbes in Dingshan and Jiaoshiba areas was made, indicating that the identified potential oil and gas indicating bacteria deserve further study.